Factors associated with the presence of extended spectrum Beta-Lactamase producing pathogens in urinary tract infections in a private clinic in Lima, Peru - Apolaya Segura, Moisés (2020)
Introduction: Urinary tract infections (utis) are the second most frequent reason for healthcare visits, and antibiotic resistance among gram-negative bacteria of the Enterobacteriaceae family has increased significantly worldwide. The emergence of microorganisms that produce extended-spectrum beta-lactamase (esbl) is especially problematic. This study aims to identify factors associated with the presence of uti caused by esbl-producing pathogens. Material and methods: An analytical cross-sectional study was conducted, and the urine culture database from a private healthcare clinic was analyzed. Factors possibly associated with the appearance of utis due to esbl-producing pathogens were analyzed, including sex, age, number of hospitalizations, and previous utis. Results: A total of 1405 positive urine cultures were studied, 85.48% of which belonged to women. The mean age of the subjects was 39.98±24.51 years, 24.13% of whom were over 60 years old. Of these, 55.56% had been attended on an outpatient basis. Almost half (49.18%) of the cultures tested positive for esbl-related uti, 96.58% of which had not presented with a previous uti. A statistically significant association was found between sex and the development of uti caused by esbl-producing microorganisms (p = 0.007), with the male sex having the highest association (prevalence ratio, 1.224; 95% confidence interval: 1.035–1.448). In addition, age, number of previous hospitalizations, and prior intensive care unit admissions also showed associations with uti development. No association was found with the presence of previous utis. Conclusion: A high frequency of utis were esbl-related, and the factors associated with esbl-related utis were male sex, age >60, and previous hospitalizations.